Public Policy and Gender Inequality in Brazilian Society: Considerations From the Realms of Labor, Politics and Science. - Nascimento, Janaina Xavier do (Universidade Estadual de Londrina, 2018)
The present text focuses on issues of gender inequality and public policy in Brazil today. My major goals are as follows: 1) to provide an analysis of gender inequality in Brazilian society through an examination of the three key arenas of labor, political representation and science and 2) to examine both the advances and the challenges that persist in confronting inequality through public policies on gender. To these ends, I employ secondary data, obtained from three different official sources (IBGE, TSE and CNPq). Lastly, I argue that while the policies that have been implemented can be linked to significant progress in the three above-mentioned arenas, we are still quite far from a real reversal of the current situation of deep inequality, persisting, above all, in the field of political representation.